Research of Customer Behavior Variables' Effects on Customer Loyalty: Case Study in Coffee Shop - Suryadi, Agus (KINERJA: Jurnal Manajemen Organisasi dan Industri, 2023)
Coffee is enjoyed by many groups, one of the attractions for coffee connoisseurs is the brand of the coffee itself. However, there are many factors that cause coffee connoisseurs to visit a coffee shop, this causes business people to set strategies to attract customers, especially to make customers loyal. The purpose of this study is to test and analyze whether green marketing, brand image, store atmosphere, and service quality simultaneously have a positive and significant effect on customer loyalty. Judging from the existing goals, the researcher used an associative research type with a quantitative approach, with a sample of 100 people. The technique used is accidental sampling, using a linear regression test. The results of this study stated that green marketing, brand image, store atmosphere and service quality simultaneously proved to have a positive and significant effect on customer loyalty at Starbucks Coffee Shop Bojongsari.